Histomorphological spectrum of meningeal tumours and its association with MIB-1 labelling index - Tiwari, Kavita; Kumar, Harendra; Dundy, Garima; Singh, Prashant; Gupta, Alok Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Meningiomas are extremely common, slow growing tumours originating from meningeal covering of brain and spinal cord. They are mostly encountered in middle or later adult life. Females are affected more commonly than males. Grading of meningiomas based on histological features has certain limitations in predicting exact biological behavior hence ancillary studies like immunohistochemistry can be used to predict the nature of the lesion. Methods: This prospective cross-sectional study was conducted in pathology department in our institute. Total 105 cases, diagnosed as meningioma between October 2019 to May 2021 were included in the study. Immuno-staining was performed using MIB-1 antibody against ki67 antigen. Various statistical test methods like chi square test, unpaired t test and spearman’s rho correlation were used to evaluate the significant value. Results: Among 105 patients analysed there were 78.09% females (mean LI 4.01±3.25%) and 21.91% males (mean LI 3.17±2.64%). Mean age of presentation was 53.14 years and most common subtype was transitional meningioma with 51.43% cases. Histological grading revealed 95.24% WHO grade 1 tumor (mean LI- 3.33±2.22%), 4.76% WHO grade 2 (mean LI- 13.80±2.28%) and no case of WHO grade 3. There was correlation between values of MIB-1 LI and histological grade. Some differences for MIB-1 labelling index were found among the subtypes of meningioma of same grade. Conclusions: The MIB-1 is one important tool in addition to routine histological evaluation. High MIB-1 LI indicates higher grade of meningioma.